Utility of Computed Tomography Imaging in Assessing Soleus Muscle Viability for Flap Coverage - Nikhil Patel, BS; Aaron S. Cohen, BS; Griffin Harris, BS; Nicholas Mercier, MD; Sara J. Stewart, MD; Emily Finkelstein, MD; Olivia B. de Araujo, MD; Jean Jose, DO; Natalia Fullerton, MD, MS (Plastic and Reconstructive Surgery, Global Open, 2025)
Background:. The use of soleus muscle flaps for traumatic middle-third injuries to the lower leg can have variable viability, as there is no standardized way to evaluate the muscle before flap selection. This case series investigated both the utility and accuracy of computed tomography angiogram (CTA) imaging in determining the viability of the soleus muscle for reconstructive use after traumatic injuries of the lower extremity. Methods:. An international review board–approved retrospective chart review was conducted of patients who underwent lower extremity soleus-based flap reconstruction by a single surgeon from January 2020 to December 2022. Patient demographics, comorbidities, and postoperative complications were recorded. Preoperative CTA reports were reanalyzed by a blinded musculoskeletal radiologist. Descriptive statistics were performed. Results:. Five patients underwent lower extremity flap reconstruction with soleus muscle over the study period. All patients had lower extremity Gustilo type IIIB or IIIC open fractures. Four out of 5 patients showed no signs of muscle injury on CTA; of those, 2 did not develop postoperative complications, and 2 required repeated irrigation and debridement, but no alternative flap coverage. One patient with preoperative CTA demonstrating soleus muscle injury developed postoperative complications requiring alternate flap reconstruction. Conclusions:. Further research is required to determine a statistically significant correlation between soleus muscle injury on preoperative CTA and postoperative complications. However, this case series illustrated the need for larger studies and a computed tomography–based standardized grading system for traumatic muscle injury to better predict soleus flap survival.